99.7k views
4 votes
If A+B+C=
\pi show that tan A + tan B +tan C = tan A.tan B.tan C

1 Answer

2 votes

Answer:


a + b + c = \pi \\ = > c= \pi - a - b \\ < = > \tan(c) = \tan(\pi - a - b) = -\tan(a + b)

Explanation:

we have:


\tan(a) + \tan(b) + \tan(c) \\ = \tan(a) + \tan(b) - \tan(a + b) \\ = \tan( a) + \tan(b) - ( \tan(a) + \tan(b) )/(1 - \tan(a) \tan(b) ) \\ = ( ( \tan(a) + \tan(b) ) \tan(a) \tan(b) )/( \tan(a) \tan(b) - 1 ) (1)

we also have:


\tan(a) \tan(b) \tan(c) \\ = - \tan(a) \tan(b) \tan(a + b) \\ = ( -(\tan( a ) + \tan(b) ) \tan(a) \tan(b) )/(1 - \tan(a) \tan(b) ) \\ = (( \tan(a) + \tan(b)) \tan(a) \tan(b) )/( \tan(a) \tan(b) - 1 ) (2)

from (1)(2) => proven

User Debapriya Biswas
by
5.8k points